The "COVID effect" in culture-based clinical microbiology: Changes induced by COVID-19 pandemic in a Hungarian tertiary care center - László Orosz; Katalin Burián (Elsevier, 2024)
Background: The presence of bacterial and fungal coinfections plays an important role in the mortality of patients with coronavirus 2019 (COVID-19). We compared data from the 3 years before and 3 years after the COVID-19 pandemic outbreak to evaluate its effect on the traits of bacterial and fungal diseases. Methods: We retrospectively collected and analyzed data on positive respiratory tract samples (n = 13,133 samples from 7717 patients) and blood cultures (n = 23,652 from 9653 patients) between 2017 and 2022 from the Clinical Center of the University of Szeged, Hungary. We also evaluated antimicrobial susceptibility test results derived from 169,020 respiratory samples and 549,729 blood cultures to gain insight into changes in antimicrobial resistance. Results: The most common respiratory pathogen in the pre-COVID era was Pseudomonas aeruginosa, whereas Candida albicans was the most frequent during the pandemic. The number of respiratory isolates of Acinetobacter baumannii was also markedly increased. In blood cultures, Staphylococcus epidermidis, Escherichia coli, and S. aureus were dominant during the study period, and A. baumannii was widespread in blood cultures during the pandemic years. Resistance to ofloxacin, penicillin, piperacillin-tazobactam, ceftazidime, cefepime, imipenem, ceftolozane-tazobactam, and itraconazole increased significantly in the COVID era. Conclusions: During the COVID-19 pandemic, there were changes in the prevalence of respiratory and blood culture pathogens at the Clinical Center of the University of Szeged. C. albicans became the predominant respiratory pathogen, and the number of A. baumannii isolates increased dramatically. Additionally, antimicrobial resistance notably increased during this period.